Super strong interface adhesion, anti-swelling hydrophilic coating and preparation method and application thereof
By introducing a hydrophobic polymer network into the hydrophilic polymer network, a uniform heterogeneous network is formed, which solves the problems of insufficient interface adhesion and poor swelling resistance of existing hydrophilic coatings, and achieves super interface adhesion and hydrophilic coating with anti-swelling properties.
Patent Information
- Application Number
- CN202210152283.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-02-18
AI Technical Summary
Due to insufficient interface adhesion, existing hydrophilic coatings are prone to fall off in a long-term or high-humidity environment, and have poor swelling resistance, resulting in a decrease in light transmittance and loss of components.
The hydrophobic polymer network is introduced into the hydrophilic polymer network, and the co-solvent is used to form a uniform heterogeneous network. The hydrophobic polymer network forms a strong interaction with the interface, limiting the swelling of the hydrophilic polymer network.
It achieves super strong interface adhesion and swelling resistance, avoids coating shedding and light transmittance, and enhances the usability and functionality of the coating.
Smart Images

Figure CN116656162B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation and processing of functional coatings and thin film materials, and specifically relates to a super-strong interface adhesion, anti-swelling hydrophilic coating and a preparation method and application thereof. Background Art
[0002] A hydrophilic coating is a type of coating that combines hydrophilic components on a substrate in an appropriate manner, thereby changing the physical and chemical properties of the substrate and achieving special functionalization. A highly hydrophilic coating can allow water to spread rapidly on the surface of the coating when it comes into contact with water, without forming independent water droplets. At present, coatings with good hydrophilicity have been widely used in biomedicine, anti-fog, self-cleaning, oil-water separation and other fields. For example, applying a hydrophilic coating on the surface of medical catheters, guide wires, stent delivery systems, etc. can reduce the friction of contact with tissues and reduce pain; applying a hydrophilic coating on the surface of glass or optical resin can induce water droplets to spread on the surface in a thin film condensation manner to achieve anti-fog; preparing a hydrophilic coating into a hydrophilic ultrafiltration membrane can cause pollutants such as colloids, oils, and proteins to aggregate into spheres on the membrane surface and detach from the surface to achieve efficient oil-water separation.
[0003] Since polymers are easy to shape and process, large-scale preparation, and relatively low in cost, constructing hydrophilic polymers on the surface is a common method for preparing hydrophilic coatings. Most hydrophilic polymer coatings are prepared by coating a hydrophilic polymer solution on the surface of a cleaned substrate and using it directly after drying. However, in this method, the adhesion between the coating and the substrate material is often only through weak physical interactions, and it is easy to fall off when used for a long time or repeatedly. For example, a coating coated on the surface of glass using the hydrophilic polymer polyvinyl alcohol will break at the interface, produce wrinkles, and lose its performance when used for a long time; at the same time, due to weak interfacial adhesion, the strategy of increasing the thickness of the coating to improve the usability is limited, such as the strategy of increasing the thickness of the hydrophilic coating to extend its anti-fog effect has little effect; in addition, the decrease in light transmittance and component loss caused by the swelling of the hydrophilic polymer in a high humidity environment is also one of the reasons that restrict the application of the coating. For example, polyglycerol fatty acid esters are attached to the surface of a polyethylene film through an adhesive as an anti-fog agent. Due to the loss of hydrophilic components, the effective period of the anti-fog film is shortened. Using interfacial chemical modification to increase the interaction between the interface and the hydrophilic polymer is a common strategy for constructing hydrophilic polymer coatings with strong adhesion, such as coating polyacrylamide on a surface modified by the silane coupling agent KH570. However, this method requires surface modification in advance, which increases the operation steps and costs, is not conducive to large-scale preparation, and has certain requirements on the surface substrate material. For example, it is only applicable to surfaces containing a large number of hydroxyl groups such as glass and ceramics, but has limited effect on general polymer substrates.
[0004] Therefore, there is an urgent need for a hydrophilic polymer coating technology that is simple to operate, suitable for interfaces of different materials, and easy to apply on a large scale, with strong interfacial adhesion and anti-swelling properties. Summary of the invention
[0005] The object of the present invention is to provide a hydrophilic coating with super strong interfacial adhesion and anti-swelling performance and its preparation method and application. By introducing a hydrophobic polymer network into a hydrophilic polymer network, and using a co-solvent to dissolve it to promote it to form a uniform heterogeneous network, wherein the hydrophobic polymer network is connected to the interface with a strong interaction (such as chemical bonds, topological entanglement), while limiting the swelling of the hydrophilic polymer network, so as to solve the problem that the hydrophilic coating prepared by coating a hydrophilic polymer forms wrinkles due to insufficient interfacial adhesion, the interface falls off, or the use performance decreases due to the decrease in transmittance caused by swelling and the loss of components. Due to the strong interfacial adhesion and anti-swelling performance, the hydrophilic coating can be prepared into a thicker functional coating compared to a traditional hydrophilic coating to increase the function of the coating. Since a variety of mechanisms for enhancing the interface effect can be provided, the coating can be covalently bonded on inorganic surfaces such as glass, ceramics, and metals, and combined in a molecular chain topological entanglement mode on the organic polymer surface, becoming a general formula for constructing a hydrophilic polymer coating on surfaces of different properties. In addition, the hydrophilic coating has a simple preparation process, can be used multiple times in a high humidity environment, and has a smooth surface and high transparency. The hydrophilic / hydrophobic heterogeneous network polymer has broad application prospects in anti-fog coatings, underwater adhesion, and biomedicine.
[0006] The technical solution of the present invention is as follows:
[0007] A hydrophilic coating composition, the composition comprising, by weight, 2-15 parts of a hydrophilic polymer, 0.1-10 parts of a hydrophobic monomer as shown in Formula 1, 0.0001-0.5 parts of an initiator, and 20-70 parts of a cosolvent;
[0008] R a (CH 2 ) n Si(OR b ) 3 Formula 1
[0009] Among them, R a represents a group containing a polymerizable functional group, wherein the polymerizable functional group includes an addition polymerizable functional group, such as a carbon-carbon double bond, a carbon-carbon triple bond; a condensation polymerizable functional group, such as an amino group, a carboxyl group, an aldehyde group, and a hydroxyl group; a ring-opening polymerizable functional group, such as a 3-20-membered epoxy group, a 4-20-membered lactone group, and a 4-20-membered lactam group. Specifically, R a At least one selected from vinyl, ethynyl, amino, methacryloyloxy, hydroxyl, and glycidyl ether groups;
[0010] Rb The same or different, independently selected from C 1-12 Alkyl, -C 1-12 Alkylene-OC 1-12 alkyl,
[0011] n is 0-12, preferably 1-8, more preferably 1-3.
[0012] According to the present invention, R a Preferably, it is a methacryloyloxy group or a glycidyl ether group;
[0013] R b Preferably, they are the same and are selected from C 1-6 Alkyl, -C 1-6 Alkylene-OC 1-6 alkyl.
[0014] Illustratively, the hydrophobic monomer represented by Formula 1 is KH570, KH171, KH172, KH151 or glycidyloxypropyltrimethoxysilane.
[0015] According to the present invention, preferably, the composition comprises 3-10 parts of a hydrophilic polymer, 0.15-4 parts of a hydrophobic monomer as shown in Formula 1, 0.015-0.04 parts of an initiator and 30-60 parts of a co-solvent.
[0016] According to the present invention, the hydrophilic polymer contains hydrophilic groups such as hydroxyl, carboxyl, and amino, and is at least one of polyvinyl alcohol, polyacrylamide, polyacrylic acid, sodium polyacrylate, polyethylene oxide, etc. Polyvinyl alcohol is preferred.
[0017] According to the present invention, the number average molecular weight of the hydrophilic polymer is 1,000 to 500,000, preferably 5,000 to 100,000, for example, 5,000, 50,000, or 100,000.
[0018] Exemplarily, the combination of the hydrophilic polymer and the hydrophobic monomer can be: the hydrophilic polymer is polyvinyl alcohol, and the hydrophobic monomer is polymerizable silane coupling agent KH570; the hydrophilic polymer is polyacrylamide, and the hydrophobic monomer is polymerizable silane coupling agent KH171; the hydrophilic polymer is polyethylene oxide, and the hydrophobic monomer is polymerizable silane coupling agent KH172.
[0019] According to the present invention, the mass ratio of the hydrophilic polymer to the hydrophobic monomer is 51%:49% to 99%:1%, preferably 80%:20% to 90%:10%.
[0020] According to the present invention, the co-solvent may be dimethyl sulfoxide, N,N-dimethylformamide, chloroform, tetrahydrofuran, toluene, ethanol, ethylene glycol, and the like.
[0021] According to the present invention, the mass ratio of the cosolvent to the total amount of the hydrophilic polymer and the hydrophobic monomer is 99%:1% to 50%:50%, preferably 70%:30% to 90%:10%.
[0022] According to the present invention, a suitable co-solvent can be selected to inhibit the hydrogen bond interactions within and between polymers when the co-solvent dissolves the polymer, and more hydrogen bonds within and between polymers are re-formed in the process of water replacing the co-solvent, thereby increasing the crosslinking density. For example, a composition system in which the hydrophilic polymer is polyvinyl alcohol, the hydrophobic monomer is silane coupling agent KH570, and the co-solvent is dimethyl sulfoxide is preferred.
[0023] According to the present invention, the initiator may be an oil-soluble thermal initiator or a photoinitiator; the thermal initiator may be, for example, azobisisobutyronitrile, dibenzoyl peroxide, etc.; the photoinitiator may be, for example, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-methylphenylpropane-1-one, benzoin dimethyl ether, etc. The mass percentage of the initiator is 0.1%-5%, preferably 0.5%-1%, of the hydrophobic monomer.
[0024] A hydrophilic coating is prepared from the hydrophilic coating composition.
[0025] According to the present invention, the hydrophilic polymer, the hydrophobic monomer and the initiator are dissolved in a co-solvent, the hydrophobic monomer is subsequently polymerized, and then placed in water for one or more water replacements to prepare the hydrophilic coating.
[0026] According to the present invention, in the hydrophilic coating, the hydrophilic macromolecules become the main polymer network, the hydrophobic monomers are polymerized to form a hydrophobic second network, and the co-solvent is used to dissolve the two to form a uniform heterogeneous network.
[0027] According to the present invention, the hydrophilic / hydrophobic heterogeneous network may have a variety of component ratios, for example, the mass ratio of the hydrophilic network to the hydrophobic network may be 51%:49% to 99%:1%, preferably 80%:20% to 90%:10%.
[0028] In the present invention, the hydrophilic polymer and the hydrophobic monomer are first dissolved in a co-solvent, and the hydrophobic monomer forms a uniform heterogeneous network with the hydrophilic polymer after polymerization, and the decrease in light transmittance caused by phase separation will not occur.
[0029] According to the present invention, the average light transmittance of the hydrophilic coating in the visible light range is greater than 85%. The wavelength of visible light is 400-800nm.
[0030] According to the present invention, the hydrophilic coating has excellent anti-swelling performance, and after swelling in water for 60 minutes, the mass and volume changes of the hydrophilic coating of the present invention do not exceed 150%. Specifically, after swelling in water for 60 minutes, the mass swelling rate and volume swelling rate of the hydrophilic coating of the present invention are 86±11% and 133±17%, respectively, while the mass swelling rate and volume swelling rate of the hydrophilic coating without introducing the hydrophobic network are 144±14% and 196±12%, respectively.
[0031] According to the present invention, the hydrophilic coating has excellent cyclic performance and remains stable during 7 dry-wet transition cycles, with the mass swelling rate maintained at 80%±10% and the volume swelling rate maintained at 130%±10%.
[0032] According to the present invention, the hydrophilic coating can be used for bonding interfaces of the same or different substrates, such as inorganic material interface / inorganic material interface, organic material interface / inorganic material interface, and organic material interface / organic material interface, and can maintain strong bonding for a long time underwater. For example, it can be used for bonding glass plates to glass plates, PMMA plates to PMMA plates, glass to PMMA plates, glass to steel plates, ceramics to PU plates, etc.
[0033] According to the present invention, the hydrophilic coating has strong interface adhesion, and the underwater adhesion strength is 800KPa to 1300KPa.
[0034] According to the present invention, the hydrophilic coating has an excellent anti-fogging effect. After being placed in a 60° C. water vapor environment from a 25° C. indoor environment for 10 minutes, no water droplets appear.
[0035] According to the present invention, the thickness of the hydrophilic coating is 10 nm to 1 mm, preferably 1 μm to 500 μm, exemplarily 25 μm, 100 μm, 200 μm, preferably 100 μm.
[0036] The present invention also provides a method for preparing the hydrophilic coating, the method comprising the following steps:
[0037] The hydrophilic polymer, the hydrophobic monomer and the initiator are dissolved in a co-solvent, and then the hydrophobic monomer is polymerized, and then placed in water for one or more water replacements to prepare the hydrophilic coating.
[0038] Specifically, the preparation method comprises the following steps:
[0039] (1) dissolving a hydrophilic polymer, a hydrophobic monomer, and an initiator in a co-solvent to prepare a mixed solution;
[0040] (2) coating the mixed solution in step (1) on a substrate, then initiating polymerization of the hydrophobic monomer, then placing in water for one or more water replacements, and drying to obtain the hydrophilic coating.
[0041] According to the present invention, in step (1), the hydrophobic monomer mixed with the initiator or the hydrophobic monomer is slowly added to the co-solvent in a dropwise manner.
[0042] Exemplarily, step (1) is carried out at room temperature, and no polymerization reaction occurs in step (1). If the initiator in step (1) is a photoinitiator, room temperature conditions are required to avoid light.
[0043] According to the present invention, in step (2), the substrate is at least one of an organic substrate or an inorganic substrate, the organic substrate is at least one of polymethyl methacrylate (PMMA), polyurethane (PU), polyethylene (PE), etc., and the co-solvent can be selected from chloroform, acetone, toluene, etc.; at this time, since the co-solvent causes the surface of the organic substrate to swell, part of the hydrophobic monomers penetrate into the interior, and after polymerization, the formed hydrophobic polymer is strongly bonded to the substrate in a topological entanglement manner, and then placed in water for one or more water replacements to increase the anti-swelling performance of the polymer network, and the hydrophilic coating is obtained after drying;
[0044] The inorganic substrate is at least one of glass, metal, ceramic, etc. The selection of the co-solvent does not affect the properties of the substrate. After heating or light exposure, the hydrophobic monomer is polymerized, and then placed in water for one or more water replacements to increase the anti-swelling performance of the polymer network. At the same time, the siloxane groups in the hydrophobic monomer dehydrate and condense with the hydroxyl groups on the inorganic substrate under the action of water to form chemical bonds to achieve strong adhesion with the inorganic substrate, and the hydrophilic coating is obtained after drying.
[0045] According to the present invention, in step (2), the mixed solution can be coated on the surface of at least one substrate.
[0046] According to the present invention, in step (2), the polymerization of the hydrophobic monomer can be initiated by heat initiation or light initiation. Heat initiation is initiated under heating conditions, the reaction temperature is 40 to 120°C, preferably 50 to 80°C, such as 60°C, and the reaction time is 0.5 to 24 hours, preferably 1 to 12 hours; light initiation is ultraviolet light initiation polymerization, such as ultraviolet lamp irradiation; the present invention has no limitation on the power of the ultraviolet lamp, the power of the ultraviolet lamp can be 1 to 5 kW, such as 1.6 kW, 2 kW, and the reaction time is 1 min to 2 hours, preferably 5 to 60 min.
[0047] According to the present invention, in step (2), the coating method is, for example, spray coating, spin coating, blade coating, dipping, etc.
[0048] According to the present invention, in step (2), the replacement time in water is 10 min-2 h, exemplarily 20 min.
[0049] Specifically, the method comprises the following steps:
[0050] (1) dissolving a hydrophilic polymer in a co-solvent, and adding a hydrophobic monomer mixed with an initiator to prepare a mixed solution;
[0051] (2a) defoaming the mixed solution in step (1), coating it on an organic substrate (such as PMMA, PU, PP, etc.), heating or irradiating it with light to initiate polymerization of the hydrophobic monomer, then placing it in water for one or more water replacements, and drying it to obtain the hydrophilic coating;
[0052] Alternatively (2b) the mixed solution in step (1) is defoamed and then coated on an inorganic substrate (such as glass, metal, ceramic), and then heated or irradiated with light to initiate polymerization of the hydrophobic monomer, and then placed in water for one or more water replacements, and then dried to obtain the hydrophilic coating.
[0053] The present invention also provides the application of the hydrophilic coating, which is used for underwater bonding of the same or different materials, anti-fogging of precision optical instruments and camera lenses, or surface modification of medical catheters, guide wires, and stent delivery systems.
[0054] Beneficial effects of the present invention:
[0055] 1. The present invention introduces a hydrophobic polymer network into a hydrophilic polymer network, and utilizes co-solvent dispersion to promote the formation of a uniform heterogeneous network; wherein the hydrophobic polymer network restricts the swelling of the hydrophilic polymer network, thereby overcoming the problems of image distortion, reduced transmittance and component loss caused by swelling.
[0056] 2. The hydrophobic polymer network formed by the polymerization of the hydrophobic monomers of the present invention can form a strong interaction with a substrate (such as an organic or inorganic substrate), exemplified by bonding in a topological entanglement manner on an organic substrate; bonding in a chemical bonding manner on an inorganic substrate. The co-solvent is then removed by displacement with water, while the anti-swelling properties of the polymer network are increased. It can also form super strong adhesion with the interface, overcoming the problem that traditional hydrophilic coatings are easy to fall off during use due to insufficient adhesion. The hydrophilic coating of the present invention can remain intact during repeated use, and the uniformity of the heterogeneous network of the hydrophilic coating ensures the high light transmittance of the coating, and has broad application prospects in devices with high requirements for anti-fog, such as precision optical instruments or camera lenses.
[0057] 3. In the present invention, the hydrophobic monomer, initiator and hydrophilic polymer are first dissolved in a co-solvent, and the hydrophobic monomer and initiator can be evenly distributed in the system. After initiation of polymerization, a uniform hydrophobic polymer network is formed, making the entire system a uniform polymer heterogeneous network, and the transmittance decrease due to phase separation will not occur.
[0058] 4. The present invention selects a suitable co-solvent to inhibit the hydrogen bond interactions within and between polymers when the co-solvent dissolves the polymer, and re-forms more hydrogen bonds within and between polymers in the process of water replacing the co-solvent, thereby increasing the crosslinking density, such as a system in which polyvinyl alcohol is a hydrophilic polymer, KH570 is a hydrophobic monomer, and dimethyl sulfoxide is a co-solvent.
[0059] 5. The hydrophilic coating of the present invention has super strong interface adhesion and anti-swelling properties. Compared with traditional hydrophilic coatings, it can be prepared into a thicker functional coating and used in a high humidity environment to increase the usability of the coating.
[0060] 6. The hydrophilic coating of the present invention can be used for bonding interfaces of the same or different materials, such as inorganic / inorganic, organic / inorganic, and organic / organic interfaces, and can maintain high-strength bonding for a long time underwater, and has potential application prospects in the direction of underwater adhesion.
[0061] The term "3-20 membered epoxy group" refers to a saturated monovalent monocycloalkane, which contains 1 O heteroatom and has a total number of 3-20 ring atoms (eg, 3, 4, 5, 6, 7, 8, 9, 10, etc.) non-aromatic cyclic group.
[0062] The term "4-20 membered lactone group" refers to a saturated monovalent monocycloalkane, which is a non-aromatic cyclic group having a total number of 4-20 ring atoms (such as 4, 5, 6, 7, 8, 9, 10 atoms) including one ester group.
[0063] The term "4-20 membered lactam group" refers to a saturated monovalent monocycloalkane, which contains one amide group and has a total of 4-20 ring atoms (eg, 4, 5, 6, 7, 8, 9, 10, etc.) non-aromatic cyclic groups. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 The transmittance curves of the hydrophilic coating in Example 1 at different times when placed in a 60°C water bath at a room temperature of 25°C.
[0065] Figure 2 The anti-fog effect diagram of the hydrophilic coating in Example 1 at different times when placed in a 60°C water bath at 25°C room temperature environment is compared with bare glass, where "Bare" means bare glass and "Coated" means coated.
[0066] Figure 3 This is a diagram showing the anti-fogging effect of hydrophilic coatings of different thicknesses in Example 1 placed in a 60°C water bath at 25°C room temperature.
[0067] Figure 4 This is an optical microscope photograph of the polymer heterogeneous network prepared in Example 1.
[0068] Figure 5 This is a cryo-scanning electron microscope photograph of the polymer heterogeneous network prepared in Example 1.
[0069] Figure 6 The mass (left figure) and volume (right figure) swelling rate tests of the hydrophilic coatings prepared in Example 1 and Comparative Example 3 at different times.
[0070] Figure 7 This is a test of the swelling rate of the polymer heterogeneous network prepared in Example 1 at different dry-wet transition cycles.
[0071] Figure 8 It is the adhesion strength of two glass plates and two PMMA plates in Example 9 and Example 10 through overlap test.
[0072] Fig. 9 This is a diagram showing the anti-fog test effect of polyvinyl alcohol films of different thicknesses prepared from the polyvinyl alcohol aqueous solution in Comparative Example 1.
[0073] Fig.10 This is an optical microscope photograph of the hydrophilic polymer network polyvinyl alcohol and the hydrophobic monomer KH570 dispersed in water in Comparative Example 2. DETAILED DESCRIPTION
[0074] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0075] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0076] Example 1
[0077] 7.2g polyvinyl alcohol (PVA) was dissolved in 30ml dimethyl sulfoxide (DMSO) solvent at 90°C, and mechanically stirred at 100rpm for 3 hours to prepare polyvinyl alcohol dimethyl sulfoxide solution A. 30mg 1-hydroxycyclohexyl phenyl ketone was dissolved in 1ml KH570, and ultrasonically mixed to obtain solution B. Solution B was slowly added to solution A, and mechanically stirred at 100rpm for 30min in a dark condition to obtain mixed solution C. At this time, the monomers in solution C were not initiated to polymerize. Solution C was centrifuged at 5000rpm for 3 minutes to remove bubbles in solution C.
[0078] The defoamed solution C was coated on a glass substrate by blade coating, and the glass substrate was naturally dried after ultrasonic cleaning with ethanol. The glass substrate coated with solution C was placed under a UV lamp (1.6kW) for 1 hour, and then the obtained polymerized coating was soaked in water for 20 minutes, taken out and naturally dried to obtain a transparent polymer heterogeneous network coating, i.e., a hydrophilic coating PVA-PKH570, with an average light transmittance of 88%.
[0079] Figure 1 The transmittance curve of the hydrophilic coating in Example 1 is placed in a 60°C water bath for different times at a room temperature of 25°C. The thickness of the hydrophilic coating is 100 μm, and the anti-fog times tested are 0 min, 10 min, 20 min, 30 min, and 60 min, respectively. The transmittance of the coating tested by UV spectrophotometry can still reach 80% after 30 minutes of anti-fog test.
[0080] Figure 2 The anti-fog effect diagram of the hydrophilic coating in Example 1 at 25°C in a 60°C water bath at different times. The test time is 10s, 1min, and 5min, respectively, and is compared with bare glass. Figure 2 The left images in the three figures are all bare glass. For bare glass, obvious water vapor appears on the glass surface after 10 seconds, while the surface coated with hydrophilic coating remains transparent after 5 minutes.
[0081] Figure 3 The anti-fog effect diagram of the hydrophilic coatings of different thicknesses in Example 1 placed in a 60°C water bath at 25°C room temperature environment, the thicknesses of the hydrophilic coatings are 25μm, 100μm, and 200μm, respectively. The results show that the hydrophilic coatings of different thicknesses maintain high transparency in the anti-fog tests of 5min, 10min, and 10min, respectively.
[0082] Figure 4This is an optical microscope photograph of the hydrophilic polymer network polyvinyl alcohol and the hydrophobic monomer KH570 uniformly mixed in the co-solvent dimethyl sulfoxide in Example 1, wherein the oil phase is stained with Sudan III. The results show that the hydrophobic monomer is uniformly dispersed in the hydrophilic polymer network without phase separation.
[0083] Figure 5 This is a cryo-scanning electron microscope photo of the hydrophilic coating prepared in Example 1. The results show that the network structure is uniform and dense.
[0084] Figure 6 The mass (left figure) and volume (right figure) swelling rate tests of the coatings prepared in Example 1 and Comparative Example 3 at different times (0min, 2min, 5min, 10min, 30min, 60min, respectively) are shown in the following figure. The specific test process is to immerse the hydrophilic coating in water, and use a microbalance and a vernier caliper to test the mass and volume at different immersion times, respectively. The results show that after swelling in water for 60min, the mass swelling rates of the coatings prepared in Example 1 and Comparative Example 3 are 86±11% and 144±14%, respectively, and the volume swelling rates are 133±17% and 196±12%, respectively, indicating that the hydrophilic coating prepared in Example 1 has good anti-swelling properties.
[0085] Figure 7 The swelling rate test of the polymer heterogeneous network prepared in Example 1 at different dry (D)-wet (W) transition cycles was performed. The dry mass and volume test was measured after placing it in a 60°C oven for 24 hours, and the wet mass and volume test was measured after immersing it in water for 24 hours. The results showed that it remained stable during 7 dry-wet transition cycles, with the mass swelling rate remaining at 80%±10% and the volume swelling rate remaining at 130%±10%, indicating good cyclic usability.
[0086] Example 2
[0087] 7.2g polyacrylamide was dissolved in 60ml N,N-dimethylformamide solvent at 90℃, and mechanically stirred at 100rpm for 3 hours to prepare N,N-dimethylformamide solution A of polyacrylamide. 15mg benzoin dimethyl ether was dissolved in 0.5ml KH570, and ultrasonically mixed to obtain solution B. Solution B was slowly added to solution A, and mechanically stirred at 100rpm for 30min in a dark environment to obtain mixed solution C. At this time, the monomers in solution C were not initiated to polymerize. Solution C was centrifuged at 5000rpm for 3 minutes to remove the bubbles in solution C.
[0088] The defoamed solution C was coated on a glass substrate by blade coating, and the glass substrate was naturally dried after ultrasonic cleaning with ethanol. The glass substrate coated with solution C was placed under a UV lamp (1.6kW) for 1 hour, and then the obtained polymerized coating was soaked in water for 20 minutes, taken out and naturally dried to obtain a transparent polymer heterogeneous network coating, i.e., a hydrophilic coating.
[0089] Example 3
[0090] Dissolve 7.2g of polyvinyl alcohol in 30ml of dimethyl sulfoxide solvent at 90°C, stir mechanically at 100rpm for 3 hours, prepare polyvinyl alcohol dimethyl sulfoxide solution A, dissolve 30mg of azobisisobutyronitrile in 1ml of KH570, mix evenly by ultrasonication to obtain solution B, slowly add solution B to solution A, stir mechanically at 100rpm for 30min in a dark environment to obtain mixed solution C. At this time, the monomers in solution C are not initiated to polymerize. Centrifuge solution C at 5000rpm for 3 minutes to remove bubbles in solution C.
[0091] The defoamed solution C is coated on a glass substrate by blade coating, and the glass substrate is cleaned with ethanol ultrasonically and then dried naturally. The glass substrate coated with solution C is placed in a 60°C oven for 2 hours, taken out and allowed to stand at room temperature. The obtained polymerized coating is then soaked in water for 20 minutes, taken out and dried naturally to obtain a transparent polymer heterogeneous network coating, i.e., a hydrophilic coating.
[0092] Example 4
[0093] 3.6 g of polyvinyl alcohol was dissolved in 60 ml of dimethyl sulfoxide solvent at 90°C, and mechanically stirred at 100 rpm for 3 hours to prepare polyvinyl alcohol dimethyl sulfoxide solution A, 2 mg of 1-hydroxycyclohexyl phenyl ketone was dissolved in 0.2 ml of KH171, and ultrasonically mixed to obtain solution B, and solution B was slowly added to solution A, and mechanically stirred at 100 rpm for 30 minutes in a dark environment to obtain mixed solution C. At this time, the monomers in solution C were not initiated to polymerize. Solution C was centrifuged at 5000 rpm for 3 minutes to remove bubbles in solution C.
[0094] The defoamed solution C was coated on a glass substrate by blade coating, and the glass substrate was naturally dried after ultrasonic cleaning with ethanol. The glass substrate coated with solution C was placed under a UV lamp (1.6kW) for 1 hour, and then the obtained polymerized coating was soaked in water for 20 minutes, taken out and naturally dried to obtain a transparent polymer heterogeneous network coating, i.e., a hydrophilic coating.
[0095] Example 5
[0096] 3.6g polyvinyl alcohol was dissolved in 60ml N,N-dimethylacetamide solvent at 90℃, and mechanically stirred at 100rpm for 3 hours to prepare polyvinyl alcohol N,N-dimethylacetamide solution A. 30mg azobisisobutyronitrile was dissolved in 1ml KH172, and ultrasonically mixed to obtain solution B. Solution B was slowly added to solution A, and mechanically stirred at 100rpm for 30min in a dark environment to obtain mixed solution C. At this time, the monomers in solution C were not initiated to polymerize. Solution C was centrifuged at 5000rpm for 3 minutes to remove the bubbles in solution C.
[0097] The defoamed solution C is coated on a glass substrate by blade coating, and the glass substrate is cleaned with ethanol ultrasonically and then dried naturally. The glass substrate coated with solution C is placed in a 60°C oven for 2 hours, taken out and allowed to stand at room temperature. The obtained polymerized coating is then soaked in water for 20 minutes, taken out and dried naturally to obtain a transparent polymer heterogeneous network coating, i.e., a hydrophilic coating.
[0098] Example 6
[0099] 7.2g polyacrylamide was dissolved in 30ml chloroform solvent at 90℃, and mechanically stirred at 100rpm for 3 hours to prepare chloroform solution A of polyacrylamide. 10mg 1-hydroxycyclohexylphenyl ketone was dissolved in 1ml KH570, and ultrasonically mixed to obtain solution B. Solution B was slowly added to solution A, and mechanically stirred at 100rpm for 30min in a dark condition to obtain mixed solution C. At this time, the monomers in solution C were not initiated to polymerize. Solution C was centrifuged at 5000rpm for 3 minutes to remove bubbles in solution C.
[0100] The defoamed solution C was coated on a glass substrate by blade coating, and the glass substrate was naturally dried after ultrasonic cleaning with ethanol. The glass substrate coated with solution C was placed under a UV lamp (1.6kW) for 1 hour, and then the obtained polymerized coating was soaked in water for 20 minutes, taken out and naturally dried to obtain a transparent polymer heterogeneous network coating, i.e., a hydrophilic coating.
[0101] Example 7
[0102] 7.2g polyacrylamide was dissolved in 30ml chloroform solvent at 90℃, and mechanically stirred at 100rpm for 3 hours to prepare chloroform solution A of polyacrylamide. 30mg azobisisobutyronitrile was dissolved in 1ml KH570, and ultrasonically mixed to obtain solution B. Solution B was slowly added to solution A, and mechanically stirred at 100rpm for 30min in a dark condition to obtain mixed solution C. At this time, the monomers in solution C were not initiated to polymerize. Solution C was centrifuged at 5000rpm for 3 minutes to remove bubbles in solution C.
[0103] The defoamed solution C is coated on a glass substrate by blade coating, and the glass substrate is cleaned with ethanol ultrasonically and then dried naturally. The glass substrate coated with solution C is placed in a 60°C oven for 2 hours, taken out and allowed to stand at room temperature. The obtained polymerized coating is then soaked in water for 20 minutes, taken out and dried naturally to obtain a transparent polymer heterogeneous network coating, i.e., a hydrophilic coating.
[0104] Example 8
[0105] 7.2g of polyvinyl alcohol was dissolved in 30ml of dimethyl sulfoxide solvent at 90°C, and mechanically stirred at 100rpm for 3 hours to prepare dimethyl sulfoxide solution A of polyvinyl alcohol. 30mg of 1-hydroxycyclohexyl phenyl ketone was dissolved in 1ml of KH570, and ultrasonically mixed to obtain solution B. Solution B was slowly added to solution A, and mechanically stirred at 100rpm for 30min in a dark condition to obtain mixed solution C. At this time, the monomers in solution C were not initiated to polymerize. Solution C was centrifuged at 5000rpm for 3 minutes to remove bubbles in solution C.
[0106] The defoamed solution C was applied to a PMMA substrate by spin coating, and the PMMA substrate was naturally dried after ultrasonic cleaning with ethanol. The PMMA substrate coated with solution C was placed under a UV lamp (1.6 kW) for 1 hour, and then the PMMA plate was taken out and placed in water to replace the residual dimethyl sulfoxide for three days, so that a strong adhesion transparent coating could be prepared on the PMMA substrate.
[0107] Example 9
[0108] 7.2g of polyvinyl alcohol was dissolved in 30ml of dimethyl sulfoxide solvent at 90°C, and mechanically stirred at 100rpm for 3 hours to prepare dimethyl sulfoxide solution A of polyvinyl alcohol. 30mg of 1-hydroxycyclohexyl phenyl ketone was dissolved in 1ml of KH570, and ultrasonically mixed to obtain solution B. Solution B was slowly added to solution A, and mechanically stirred at 100rpm for 30min in a dark condition to obtain mixed solution C. At this time, the monomers in solution C were not initiated to polymerize. Solution C was centrifuged at 5000rpm for 3 minutes to remove bubbles in solution C.
[0109] The defoamed solution C was directly coated in the middle of two glass plates to achieve the overlap of the two glass plates. Both glass plates were cleaned with ethanol ultrasonic and then dried naturally. The glass plates coated with solution C were placed under a UV lamp (1.6kW) for 1.5 hours, and then the two glass plates were taken out and placed in water for three days to replace the residual dimethyl sulfoxide, so that the two glass substrates could be strongly bonded.
[0110] Example 10
[0111] Dissolve 7.2g of polyvinyl alcohol in 30ml of dimethyl sulfoxide solvent at 90°C, stir mechanically at 100rpm for 3 hours, prepare polyvinyl alcohol dimethyl sulfoxide solution A, dissolve 30mg of 1-hydroxycyclohexyl phenyl ketone in 1ml of KH570, mix ultrasonically to obtain solution B, slowly add solution B to solution A, stir mechanically at 100rpm for 30min in dark conditions to obtain mixed solution C. At this time, the monomers in solution C are not initiated to polymerize. Centrifuge solution C at 5000rpm for 3 minutes to remove bubbles in solution C.
[0112] The defoamed solution C was applied to two PMMA substrates by spin coating, and the two PMMA substrates were cleaned with ethanol ultrasonic and then dried naturally. The two PMMA plates coated with solution C were placed under a UV lamp (1.6kW) for 1 hour, and then the two PMMA plates were taken out and placed in water for three days to replace the residual dimethyl sulfoxide, so that the two PMMA substrates could be strongly bonded.
[0113] Figure 8 In order to test the adhesion strength of the hydrophilic coating to different substrates by overlapping the two glass plates and the two PMMA plates in Example 9 and Example 10, a universal mechanical tensile tester was used to fix the two ends of the two substrates respectively, and then a tensile test was performed. The results of tensile measurement of adhesion strength showed that the underwater adhesion strength of the two glass plates and the two PMMA plates bonded by the polymer of the hydrophilic coating was 1153±58KPa and 987±178KPa, respectively.
[0114] Embodiment 11
[0115] Dissolve 7.2g of polyvinyl alcohol in 30ml of dimethyl sulfoxide solvent at 90°C, stir mechanically at 100rpm for 3 hours, prepare polyvinyl alcohol dimethyl sulfoxide solution A, dissolve 30mg of 1-hydroxycyclohexyl phenyl ketone in 1ml of KH570, mix ultrasonically to obtain solution B, slowly add solution B to solution A, stir mechanically at 100rpm for 30min in dark conditions to obtain mixed solution C. At this time, the monomers in solution C are not initiated to polymerize. Centrifuge solution C at 5000rpm for 3 minutes to remove bubbles in solution C.
[0116] The defoamed solution C was applied to two aluminum plates by spin coating, and the aluminum plates were naturally dried after ultrasonic cleaning with ethanol. The two aluminum plates coated with solution C were placed under a UV lamp (1.6kW) for 1 hour, and then the two aluminum plates were taken out and placed in water for three days to replace the residual dimethyl sulfoxide, so that the two aluminum plates could be strongly bonded.
[0117] Example 12
[0118] 7.2g of polyvinyl alcohol was dissolved in 30ml of dimethyl sulfoxide solvent at 90°C, and mechanically stirred at 100rpm for 3 hours to prepare dimethyl sulfoxide solution A of polyvinyl alcohol, 30mg of 1-hydroxycyclohexyl phenyl ketone was dissolved in 1ml of KH570, and ultrasonically mixed to obtain solution B, and solution B was slowly added to solution A, and mechanically stirred at 100rpm for 30min in a dark condition to obtain mixed solution C. At this time, the monomers in solution C were not initiated to polymerize. Solution C was centrifuged at 5000rpm for 3 minutes to remove bubbles in solution C.
[0119] The defoamed solution C was directly coated between the glass and the PMMA plate to achieve the overlap of the two different substrates. The glass and PMMA plates were cleaned with ethanol ultrasonically and then dried naturally. The glass and PMMA plates coated with solution C were placed under a UV lamp (1.6kW) for 1.5 hours, and then the glass and PMMA plates were taken out and placed in water for three days to replace the residual dimethyl sulfoxide, which can achieve a strong bond between the glass and PMMA plates.
[0120] Example 13
[0121] 7.2g of polyvinyl alcohol was dissolved in 30ml of dimethyl sulfoxide solvent at 90°C, and mechanically stirred at 100rpm for 3 hours to prepare dimethyl sulfoxide solution A of polyvinyl alcohol, 30mg of 1-hydroxycyclohexyl phenyl ketone was dissolved in 1ml of KH570, and ultrasonically mixed to obtain solution B, and solution B was slowly added to solution A, and mechanically stirred at 100rpm for 30min in a dark condition to obtain mixed solution C. At this time, the monomers in solution C were not initiated to polymerize. Solution C was centrifuged at 5000rpm for 3 minutes to remove bubbles in solution C.
[0122] The defoamed solution C was directly coated between the glass and the aluminum plate to achieve the overlap of the two different substrates. The glass and aluminum plates were cleaned with ethanol ultrasonically and then dried naturally. The glass and aluminum coated with solution C were placed under a UV lamp (1.6kW) for 1.5 hours, and then the glass and aluminum plates were taken out and placed in water for three days to replace the residual dimethyl sulfoxide, which can achieve a strong bond between the glass and the aluminum plate.
[0123] Comparative Example 1
[0124] 7.2 g of polyvinyl alcohol was dissolved in 30 ml of water at 90° C. and mechanically stirred at 100 rpm for 3 hours to prepare an aqueous solution of polyvinyl alcohol. The aqueous solution of polyvinyl alcohol was centrifuged at 5000 rpm for 3 minutes to remove bubbles.
[0125] The defoamed polyvinyl alcohol solution was coated on a glass substrate by scraping. The glass substrate was cleaned with ethanol ultrasonic wave and then dried naturally. The coating was dried naturally to obtain a polyvinyl alcohol film (hydrophilic coating). The average light transmittance of the hydrophilic coating was 88%.
[0126] Fig. 9 The diagram shows the effects of polyvinyl alcohol films of different thicknesses in the anti-fog test in Comparative Example 1, where the thicknesses are 25 μm, 100 μm, and 200 μm, respectively. The results show that the polyvinyl alcohol films of different thicknesses generate a large number of wrinkles in the anti-fog tests of 5 min, 10 min, and 10 min, respectively.
[0127] Pure hydrophilic coatings are bonded to the glass surface only through physical interactions. In a water-rich environment, the interface falls off due to insufficient interfacial adhesion, and wrinkles appear on the coating surface due to swelling, resulting in a decrease in light transmittance.
[0128] Comparative Example 2
[0129] 7.2 g of polyvinyl alcohol was dissolved in 30 ml of water at 90°C, and mechanically stirred at 100 rpm for 3 hours to prepare aqueous solution A of polyvinyl alcohol. 30 mg of 1-hydroxycyclohexyl phenyl ketone was dissolved in 1 ml of KH570, and ultrasonically mixed to obtain solution B. Solution B was slowly added to solution A, and mechanically stirred at 100 rpm for 30 minutes in a dark environment to obtain mixed solution C. At this time, the monomers in solution C were not initiated to polymerize. Solution C was centrifuged at 5000 rpm for 3 minutes to remove bubbles in solution C.
[0130] The defoamed solution C was coated on a glass substrate by blade coating, and the glass substrate was naturally dried after ultrasonic cleaning with ethanol. The glass substrate coated with solution C was placed under a UV lamp (1.6 kW) for 1 hour, and then the obtained polymerized coating was soaked in water for 20 minutes, taken out and naturally dried.
[0131] Fig.10 This is an optical microscope photo of the hydrophilic polymer network polyvinyl alcohol and the hydrophobic monomer KH570 dispersed in water in Comparative Example 2. The optical microscope shows that there are oil phase droplets stained by Sudan III in the system. Since the hydrophobic monomer has poor solubility in water, it is dispersed in the system in the form of oil droplets, which seriously reduces the light transmittance of the coating.
[0132] Comparative Example 3
[0133] 7.2 g of polyvinyl alcohol was dissolved in 30 ml of dimethyl sulfoxide at 90° C. and mechanically stirred at 100 rpm for 3 hours to prepare a polyvinyl alcohol dimethyl sulfoxide solution. The polyvinyl alcohol dimethyl sulfoxide solution was centrifuged at 5000 rpm for 3 minutes to remove bubbles.
[0134] The defoamed polyvinyl alcohol dimethyl sulfoxide solution was coated on a glass substrate by blade coating, and the glass substrate was naturally dried after ultrasonic cleaning with ethanol. The obtained coating was then soaked in water for 20 minutes, taken out and naturally dried.
[0135] The polyvinyl alcohol network of Comparative Example 3 is more uniform than that of the polyvinyl alcohol network of Comparative Example 1, but the problem of insufficient interfacial adhesion has not been overcome, and wrinkles and shedding still occur in a water-rich environment.
[0136] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A hydrophilic coating, characterized in that: The hydrophilic polymer, the hydrophobic monomer and the initiator are dissolved in a co-solvent, and then the hydrophobic monomer is polymerized, and then placed in water for one or more water replacements to prepare the hydrophilic coating; The hydrophilic coating is prepared from the following composition: The composition comprises, by weight, 2-15 parts of a hydrophilic polymer, 0.1-10 parts of a hydrophobic monomer, 0.0001-0.5 parts of an initiator and 20-70 parts of a co-solvent; The hydrophilic polymer contains hydroxyl, carboxyl or amino hydrophilic groups; The hydrophobic monomer is KH570, KH171, KH172, KH151 or glycidyloxypropyltrimethoxysilane; The co-solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, chloroform, tetrahydrofuran, toluene, ethanol and ethylene glycol.
2. The hydrophilic coating according to claim 1, characterized in that: The composition comprises 3-10 parts of hydrophilic polymer, 0.15-4 parts of hydrophobic monomer, 0.015-0.04 parts of initiator and 30-60 parts of co-solvent.
3. The hydrophilic coating according to claim 1, characterized in that: The hydrophilic polymer is at least one of polyvinyl alcohol, polyacrylamide, polyacrylic acid, sodium polyacrylate and polyethylene oxide.
4. The hydrophilic coating according to claim 1, characterized in that: The number average molecular weight of the hydrophilic polymer is 1,000 to 500,000.
5. The hydrophilic coating according to claim 1, characterized in that: The initiator is an oil-soluble thermal initiator or a photoinitiator; the thermal initiator is azobisisobutyronitrile and / or dibenzoyl peroxide; the photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-methylphenylpropane-1-one, and benzoin dimethyl ether.
6. The hydrophilic coating according to claim 1, characterized in that: The initiator is 0.1%-5% by weight of the hydrophobic monomer.
7. The hydrophilic coating according to claim 1, characterized in that: The average light transmittance of the hydrophilic coating in the visible light range is greater than 85%; the wavelength of the visible light is 400-800nm.
8. The hydrophilic coating according to claim 1, characterized in that: The hydrophilic coating has excellent anti-swelling performance. After swelling in water for 60 minutes, the mass swelling rate and volume swelling rate of the hydrophilic coating are 86±11% and 133±17% respectively.
9. The hydrophilic coating according to claim 1, characterized in that: The hydrophilic coating has excellent cyclic performance and remains stable during 7 dry-wet transition cycles, with the mass swelling rate maintained at 80%±10% and the volume swelling rate maintained at 130%±10%.
10. The hydrophilic coating according to claim 1, characterized in that: The hydrophilic coating is used for bonding interfaces of the same or different substrates.
11. The hydrophilic coating according to claim 10, characterized in that: The hydrophilic coating is used for bonding of inorganic material interface / inorganic material interface, organic material interface / inorganic material interface, and organic material interface / organic material interface, and can maintain strong bonding for a long time underwater.
12. The hydrophilic coating according to claim 11, characterized in that: The hydrophilic coating is used for bonding glass plates to glass plates, PMMA plates to PMMA plates, glass to PMMA plates, glass to steel plates, or ceramic to PU plates.
13. The hydrophilic coating according to claim 1, characterized in that: The hydrophilic coating has strong interface adhesion, and the underwater adhesion strength is 800KPa to 1300KPa.
14. The hydrophilic coating according to claim 1, characterized in that: The hydrophilic coating has an excellent anti-fog effect. After being placed in a 60°C water vapor environment from a 25°C indoor environment for 10 minutes, no water droplets appear.
15. The hydrophilic coating according to claim 1, characterized in that: The thickness of the hydrophilic coating is 10 nm to 1 mm.
16. The hydrophilic coating according to claim 1, characterized in that: The preparation method of the hydrophilic coating comprises the following steps: (1) dissolving a hydrophilic polymer, a hydrophobic monomer, and an initiator in a co-solvent to prepare a mixed solution; (2) coating the mixed solution in step (1) on a substrate, then initiating polymerization of the hydrophobic monomer, then placing in water for one or more water replacements, and drying to obtain the hydrophilic coating.
17. The hydrophilic coating according to claim 16, characterized in that: In step (2), the substrate is at least one of an organic substrate and an inorganic substrate, the organic substrate is at least one of polymethyl methacrylate, polyurethane, and polyethylene; the inorganic substrate is at least one of glass, metal, and ceramic.
18. Use of the hydrophilic coating according to any one of claims 1 to 17, characterized in that: It is used for underwater bonding of the same or different materials, anti-fogging of precision optical instruments and camera lenses, or surface modification of medical catheters, guidewires, and stent delivery systems.
Citation Information
Patent Citations
Preparation method of transparent and persistent form anti-fog glass and product thereof
CN104926156A
Hydrophilic treatment coating composition and hydrophilizing treatment method
CN106459614A